S02-3 Relationships between work organisation factors and carpal tunnel syndrome and epicondylitis. (1st September 2016) - Bao, Stephen; Kapellusch, Jay; Merryweather, Andrew; Thiese, Matthew; Garg, Arun; Hegmann, Kurt; Silverstein, Barbara
Abstract : Based on analyses of prevalence data on a pooled cohort of 1834 subjects from three research groups, this study examined the relationships between four work organisation variables (job rotation, overtime work, having second job and work pacing) and the three musculoskeletal health outcome measures (prevalence of carpal tunnel syndrome (CTS), lateral epicondylitis (LEPI) and medial epicondylitis (MEPI)). There were 249 prevalence CTS cases out of a total 1799 eligible subjects, 65 LEPI out of 1807 eligible subjects, and 14 MEPI out of 1812 eligible subjects in this cohort. The relationships between the work organisation factors and the health outcome variables were assessed using logistic regression models fitted by the generalised estimating equations (GEE) method to account for non-independence of data collected by the same research group. Odds ratios and 95% confidence intervals were estimated for each work organisation variable separately, while always adjusting for age, gender, and body mass index (BMI). Varied degrees of associations between these work organisation variables and the health outcome variables were found. Job rotation had significant association with CTS cases (OR = 1.23, 95%CL: 1.00–1.50). No statistically significant associations were found between the other work organisation variables and CTS cases. Contradictory to common believe, overtime work was significantly associated with lower LEPI prevalence (OR = 0.48, 95% CI: 0.28–0.84). For the LEPI, job rotation was marginally associated with LEPI cases (OR = 1.69, 95% CI: 0.96–2.97). No associations were found between having second job or different types of work pacing and LEPI. No statistically significant associations were found between the four work organisation variables and MEPI. The results demonstrated that while clear associations between many biomechanical/psychosocial factors and the musculoskeletal health outcome variables, the work organisation variables have much more complicated impact on these health outcome variables.